2017
DOI: 10.1161/jaha.117.006079
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Associations of Arterial Compliance With Coronary Artery Plaque and Calcification Burden

Abstract: BackgroundCoronary artery disease is a leading killer of women. Arterial stiffness predicts myocardial infarction, and postmenopausal women have lower arterial compliance (AC) than men. We hypothesized that lower AC would be associated with greater burden of coronary artery plaque and calcification, and that these associations would be stronger in women than men.Methods and ResultsWe evaluated 3639 consecutive adults without coronary artery disease history who had coronary computed tomography between 2006 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Yet, even in high functioning healthcare systems such as Sweden and the UK there appear to be systematic differences in the use of evidence-based medicine that disadvantages women 8. However, the QIs did not fully explain the sex differences in survival following AMI, and we also acknowledge sex differences in symptomatology, health-seeking behaviour4 5; comorbidity burden,7 vascular physiology, incidence of MINOCA6; and pharmacokinetics and pharmacodynamics 29…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Yet, even in high functioning healthcare systems such as Sweden and the UK there appear to be systematic differences in the use of evidence-based medicine that disadvantages women 8. However, the QIs did not fully explain the sex differences in survival following AMI, and we also acknowledge sex differences in symptomatology, health-seeking behaviour4 5; comorbidity burden,7 vascular physiology, incidence of MINOCA6; and pharmacokinetics and pharmacodynamics 29…”
Section: Discussionmentioning
confidence: 83%
“…For acute myocardial infarction (AMI), women have higher early mortality rates and lower longer term survival than men 2 3. Women with AMI are more likely to have non-chest pain symptoms,4 longer delays in seeking medical care following symptom onset,5 myocardial infarction with non-obstructive coronary arteries (MINOCA)6 and a different comorbidity burden 7. However, such factors may not fully explain their disadvantaged outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have demonstrated sex differences in the effects of arterial compliance on the development and impact of coronary artery disease. Specifically, lower arterial compliance (indicative of elevated arterial stiffness) is associated with a higher burden of coronary artery plaque and calcification in women not men (Coutinho et al, ). Furthermore, lower arterial compliance was also associated with impaired coronary microvascular function, as measured by myocardial flow reserve in women not men (Coutinho et al, ).…”
Section: Sex‐specific Effects Of Other Cvd‐related Pathologies On Artmentioning
confidence: 99%
“…Women also develop greater increases in pulse pressure and arterial stiffness with aging, at least some of which appears to be independent of body and aortic size (Coutinho, Borlaug, Pellikka, Turner, & Kullo, ; Dart et al, ; Mitchell et al, ). In addition, heart failure with preserved ejection fraction (HFpEF) and coronary microvascular dysfunction are the more commonly diagnosed forms of CVD in women and are associated with elevated arterial stiffness in women (Beale, Meyer, Marwick, Lam, & Kaye, ; Coutinho et al, ; Coutinho, Yam, Chow, Dwivedi, & Inacio, ). Overall, substantial sex differences are observed in the development of arterial stiffness, not only in the timing but also in the setting of CVD risk factors such as diabetes mellitus and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the current study reports of a dramatic increase in voluntary health insurance between W1 and W3. Along with CHPs, the Ministry of Health, in 2005, introduced the regenerative health and nutrition programme (RHNP) as part of its effort to curb the rising trend of NCDs [65,70] while, in 2014, the ministry collaborated with the Novartis Foundation to launch the community-based hypertension improvement program (ComHIP). This program continues to conduct community-based BP screening and BP monitoring in many parts of the country [41].…”
Section: Plos Onementioning
confidence: 99%